Bird Strike Analysis on 19 Passenger Aircraft Windshield with Different Thickness and Impact Velocity (FTK UNSURYA, 2020)
Abstrct - A Windshield is a component that must be tested to comply with the certification requirements in the bird strike phenomenon based on Civil Aviation Safety Regulations (CASR) subpart 23.775. The purpose of this study is to obtain the thickness of 19 passenger aircraft windshield that meets the certification requirements and determine the dynamic response of the windshield to impact velocity variations. The finite element is used to simulate bird strike phenomena. The elastic-plastic polymethyl methacrylate (PMMA) material with the maximum principal strain failure criterion is used to model the dynamic response of the windshield. Numerical modeling is validated, both with analytical and experimental results which are then used to investigate the effect of variations in windshield thickness and impact velocity. The results obtained that with a thickness of 9 mm, the windshield is able to withstand bird strikes based on cases that have been determined by the regulation. In addition, the impact velocity that causes the dynamic response of the windshield in the elastic, plastic deformation, and the greatest failure is the velocity of 87.5 ms-1(cruising phase). The uppermost of the windshield (fixed) is the weakest part due to the stress concentration.